Hazards of anti‐Blackness in the United States. (29th June 2022) - Rowell‐Cunsolo, Tawandra L.; Bellerose, Meghan; Haile, Rahwa
Abstract: On February 26, 2012, a Black child, Trayvon Martin, was executed in Sanford, Florida. Seventeen months later his killer was found not guilty. This is but one example of the state's brazen disregard for Black life, rooted in the kidnapping and enslavement of Africans more than 400 years ago, and the ways in which they and their descendants were systematically tortured. Trayvon Martin's murder catalyzed the Black Lives Matter (BLM) movement, which names and resists deeply entrenched state violence and inequities against Black people in the United States. In this manuscript we: (1) summarize examples of structural disregard for Black lives in the United States; (2) describe how this disregard is reflected in differential patterns of social inequities, morbidity, and mortality; and (3) discuss how we can better employ the BLM perspective to frame a more historicized understanding of patterns in population health and to envision ways to resist health inequities.